Compact circularly polarized metaresonator‐enabled deca‐band antenna. Issue 2 (1st October 2019) - Alam, Maksud; Mainuddin,; Kanaujia, Binod; Beg, Mirza; Kumar, Sachin
Abstract: In this article, a circularly polarized small‐sized deca‐band monopole antenna is proposed and investigated. The proposed antenna consists of gun‐shaped monopole radiator and split‐ring resonator (SRR) array‐loaded partial ground plane present on the top and bottom sides of the substrate, respectively. The antenna is excited by a microstrip line feed and in order to get varied multiband operation with circular polarization, several unique configurations of SRRs are employed as metaresonators. Using the approach of combining resonances of metaresonators and monopole radiator, dual‐, triple‐, hexa‐, and deca‐band operations can be achieved. The permittivity and permeability of the composite metaresonator structure made of SRRs are extracted to illustrate the working principle of the designed multiband antenna. The proposed multiband antenna covers long‐term evolution, WLAN, WiMAX, bluetooth, satellite digital audio radio system (SDARS), radio altimeter, and satellite communication C‐band applications, on a single multifunctional device, much needed in the fast‐growing wireless industry. The antenna is fabricated on a 40 × 47 × 1.5748 mm 3 RT Duroid 5880 substrate, and simulations were carried out with the help of the tool Ansys HFSS. The simulated and measured results are in good agreement.